Interactive effects of dietary fibre and lipid types modulate gastrointestinal flows and apparent digestibility of fatty acids in growing pigs. Issue 4 (11th December 2018) - Ndou, Saymore P.; Kiarie, Elijah; Walsh, Maria C.; Ames, Nancy; de Lange, Cornelis F. M.; Nyachoti, Charles M.
Abstract: A total of eight ileal and caecal cannulated Yorkshire barrows were used to determine the interactions of dietary fibre (DF) and lipid types on apparent digestibility of DM and fatty acids (FA) and FA flows in gastrointestinal segments. Pigs were offered four diets that contained either pectin or cellulose with or without beef tallow or maize oil in two Youden square designs ( n 6). Each period lasted 15 d. Faeces, ileal and caecal contents were collected to determine apparent ileal digestibility (AID), apparent caecal digestibility and apparent total tract digestibility (ATTD) of dietary components. The interactions between DF and lipid types influenced ( P <0·05) the digestibility of DM and FA flows. The addition of maize oil decreased ( P <0·05) AID of DM in pectin diets, and the addition of beef tallow depressed ( P <0·001) ATTD of DM in cellulose diets. Dietary supplementation with beef tallow decreased ( P <0·05) the AID of FA in pectin-containing diets but had no effects in cellulose-containing diets. Dietary supplementation with beef tallow increased ( P <0·05) AID of SFA and PUFA and the flow of ileal oleic, vaccenic, linolenic and eicosadienoic acids and reduced the flow of faecal lauric, docosatetraenoic and docosapentaenoic acids in pectin- and cellulose-containing diets. In conclusion, the interaction between DF type and lipid saturation modulates digestibility of DM and lipids and FA flows but differs for soluble and insoluble fibre sources, SFA and unsaturated fatty acids and varies in different gastrointestinal segments.